Pengaruh Perceived Organizational Support, Job Demands, dan Job Satisfaction terhadap Work Engagement - Muhammad Mudrik Fairnandha (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine the effect of perceived organizational support, job demands and job satisfaction on work engagement among employees of SPBU COCO PT. Pertamina Retail Ketintang and Jemursari Surabaya. This research type is causal research that uses a quantitative approach. The sampling technique is total sampling, where the entire population was used as the sample. The sample that used is 60 respondents. The statistical analysis method is multiple linear regression with the help of the SPSS version 20 application. The results show that perceived organizational support has a significant effect on work engagement. Job demands have no significant effect on work engagement. Moreover, job satisfaction has no significant effect on work engagement. The company should pay more attention to decreasing their workers' satisfaction to maintain work engagement.